The chromo shadow domain, a second chromo domain in heterochromatin-binding protein 1, HP1. - Aasland, R (1995)
The chromo domain was originally identified as a protein sequence motif common to the Drosophila chromatin proteins, Polycomb (Pc) and heterochromatin protein 1 [HP1; Paro and Hogness (1991) Proc. Natl. Acad. Sci. USA, 88, 263-267; Paro (1990) Trends Genet., 6, 416-421]. Here we describe a second chromo domain-like motif in HP1. Subsequent refined searches identified further examples of this chromo domain variant which all occur in proteins that also have an N-terminally located chromo domain. Due to its relatedness to the chromo domain, and its occurrence in proteins that also have a classical chromo domain, we call the variant the 'chromo shadow domain'. Chromo domain-containing proteins can therefore be divided into two classes depending on the presence, for example in HP1, or absence, for example in Pc, of the chromo shadow domain. We have also found examples of proteins which have two classical chromo domains. The Schizosaccharomyces pombe SWI6 protein, involved in repression of the silent mating-type loci, is a member of the chromo shadow group. The similar modular architecture of SpSW16, HP1 and HP1-like proteins supports the model that the specificity of action of chromatin proteins is generated by combinations of protein modules.